2022
DOI: 10.22146/ijc.76080
|View full text |Cite
|
Sign up to set email alerts
|

Biodecolorization of Methylene Blue by Using <i>Bacillus subtilis</i> Immobilized into SA-PVA-Bentonite Matrix in Mineral Salt Medium and Non-nutritious Medium

Abstract: Industrial dye wastewater can potentially cause significant harm to organisms and the environment across the world. Methylene blue (MB) is a synthetic dye that can be found in wastewater. Immobilizing clay material and degradative bacteria into a carrier is the best way to remove MB. Therefore, this study aimed to immobilize Bacillus subtilis in sodium alginate (SA)-polyvinyl alcohol (PVA)-Bentonite for adsorption and degrading MB in nutritious mineral salt medium (MSM) and non-nutritious media. The result sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Nabilah et al [ 25 ] successfully removed methylene blue dye using a mixture of R. pickettii bacteria and Trichoderma viride fungi immobilized into SA-PVA-Bentonite. Rohmah et al [ 28 ] also showed that B. subtilis could decolorize and degrade methylene blue dye, while according to Upendar et al [ 31 ], the bacteria were immobilized into the suitable matrix. Generally, P. aeruginosa is one of the bacteria that is often used in study focused on the degradation of dye waste, indicating its potential to degrade methylene blue, methyl orange, reactive yellow, direct orange, etc [ [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nabilah et al [ 25 ] successfully removed methylene blue dye using a mixture of R. pickettii bacteria and Trichoderma viride fungi immobilized into SA-PVA-Bentonite. Rohmah et al [ 28 ] also showed that B. subtilis could decolorize and degrade methylene blue dye, while according to Upendar et al [ 31 ], the bacteria were immobilized into the suitable matrix. Generally, P. aeruginosa is one of the bacteria that is often used in study focused on the degradation of dye waste, indicating its potential to degrade methylene blue, methyl orange, reactive yellow, direct orange, etc [ [40] , [41] , [42] ].…”
Section: Resultsmentioning
confidence: 99%
“…The culture was transferred to another LB until the optical density (OD 600 ) touched a value of 1 and incubated at 37 °C to enter a stationary phase ( P. aeruginosa : 24 h, B. subtilis : 24 h, and R. pickettii : 44 h). Finally, 50 mL of each bacteria was taken, and centrifuged to obtain the biomass [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations